Role of available adjuvant therapies following surgical resection of atypical choroid plexus papilloma—a systematic review and pooled analysis. Issue 1 (25th October 2020) - Tavallaii, Amin; Keykhosravi, Ehsan; Rezaee, Hamid; Kianbakht, Camellia
Abstract: Background: Atypical choroid plexus papilloma is a recently introduced entity with intermediate pathological characteristics. These tumors are relatively rare and the optimal management of these tumors is a matter of debate. Therefore, we performed a systematic review and pooled analysis about the effects of adjuvant therapies on outcome measures of these patients. We also compared these effects on totally and partially resected tumors and pediatric and adult populations. Methods: A systematic search of 3 databases based on inclusion/exclusion criteria was performed. Data extraction was separately performed by 2 authors, and the summarized data were presented in the form of tables. Pooled estimates of different outcome measures were calculated for each adjuvant therapy and presented separately for studies with pediatric, adult, or mixed populations. Results: A review of 14 included studies consisting of 144 patients revealed the effect of adjuvant treatment on reduction of tumor recurrence, metastasis, and reoperation rates and increasing survival rates in patients with subtotal tumor resection. This advantage was not seen in the case of gross total tumor resection. Almost all outcome measures were more favorable in the pediatric population. Conclusions: It can be concluded that whenever gross total resection is not feasible, the implementation of adjuvant therapy can improve the outcome and prognosis. In other cases, it should be decided on an individual basis. Also, more aggressive behavior and higher rates of recurrence and mortality in the adult population suggest the consideration of more aggressive adjuvant treatments for adult patients.